Methods Applied in the Prediction of Brittle Failure in Tunnels and Underground Caverns - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Tunnels and underground caverns located at greater depth (high rock cover or overburden) are subjected to high in-situ stress environment. Those rock mass that are relatively unjointed and massive are exposed to the brittle failure, which is famously known as rock spalling/ rock bursting phenomenon. Establishing state of the stress and evaluating stress-induced instability in tunnels passing through such rock mass at relatively greater depth is therefore a challenge. The aim of this manuscript is to describes existing brittle failure (rock burst) prediction methods that are being practiced worldwide and propose necessary editions so that quality of assessment is enhanced. The methods described are very practical and the author is confident that professional engineers will use them to evaluate and predict potential rock burst/ rock spalling scenario in the tunnels during planning, design and construction phases. Each method of prediction is explained, applicability extent is highlighted and comparisons between the methods are made. HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 5-9 Uploaded date: January 14, 2018